Mejorar el inglés como lengua extranjera en estudiantes de pregrado: perspectivas y estrategias para ser bilingüe (2021)
This article is a reflection on the perspectives and strategies to become bilingual from a speech and stance of two foreign native professors through a virtual conference. The objective is to develop and generate in students, in different academic professional-level programs of the University of Cundinamarca, simple ways of interaction with a foreign language. These learners show beliefs and thoughts that limit the learning which leads to a lack in the practice progress and presents low results in the activities that converge in the use of the four communicative skills of English. In this way, a deductive method is implemented and, with the brief statement of experiences lived around learning a language, causes and allows to create an autonomy of improvement in the future in the use of the language to be taken to different possible contexts of daily and professional life. Thus, the conclusions are directed to a self-instruction based on the perseverance, in the implementation of actions and interaction with own elements, incorporated or linked from areas of technology, art, science, or society.